Konsep Al-Qur’an Tentang Tazkiyatun Nafs dan Aplikasinya (Kajian Tafsir Tematik) - Budi Suhartawan (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, Cianjur, indonesia, 2025)
This study explores the Qur’anic concept of Tazkiyatun Nafs—the purification of the soul—through a thematic exegesis approach. It focuses on two principal dimensions: the cleansing of the soul from sins and negative traits, and the development of spiritual and moral potential toward akhlaq al-karimah (noble character). The Qur’an addresses nafs in multiple dimensions—ruh (spirit), qalb (heart), and ‘aql (intellect)—while acknowledging the dual nature of human potential for both righteousness and corruption. Tazkiyah is framed as a comprehensive process involving increased faith, spiritual awareness, self-restraint, introspection, and improved social relations, all of which aim to elevate the human condition and draw one closer to Allah SWT. Beyond personal development, Tazkiyatun Nafs holds wider implications for ecological and societal balance. A purified soul fosters environmental responsibility, discourages exploitation, and promotes harmonious coexistence within the broader ecosystem—aligning spiritual purification with ecological sustainability. This research argues that resolving moral and ecological crises requires more than technical interventions; it demands a return to inner transformation rooted in spiritual consciousness. Tazkiyatun Nafs thus emerges as a foundational pillar in building an integrated Muslim identity—harmonizing body and soul, while resisting materialism and hedonism. The findings recommend further interdisciplinary research connecting Qur’anic psychology, education, and sustainable development frameworks.